2021
DOI: 10.1093/neuros/nyab125
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Minimally Invasive Procedures for Mesial Temporal Lobe Epilepsy: Too Minimal, Too Fast?

Abstract: BACKGROUND Cortico-amygdalohippocampectomy (CAH) is effective for mesial temporal lobe epilepsy (mTLE). Concerns regarding surgical morbidity have generated enthusiasm for more minimally invasive interventions. A careful analysis of current data is warranted before widespread adoption of these techniques. OBJECTIVE To systematically review the use of laser interstitial thermal therapy (LITT), stereotactic radiosurgery (SRS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
0
11
1
Order By: Relevance
“…It is possible, however, that LITT effectiveness is overestimated due to a positive reporting bias associated with novel technologies (halo effect), a reluctance to publish poor outcomes, shorter follow up durations and overcoming of learning curves. A systematic review comparing only the minimally invasive techniques LITT, RF-TC and SRS concluded that LITT shows promising seizure efficacy in the short-term ( 65 ). Our linear-regression model results provide a much-needed statistical analysis of the data in comparison to open surgical methods to further support LITT as an emerging technique, but long-term follow ups and direct comparisons are needed to form a firm conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that LITT effectiveness is overestimated due to a positive reporting bias associated with novel technologies (halo effect), a reluctance to publish poor outcomes, shorter follow up durations and overcoming of learning curves. A systematic review comparing only the minimally invasive techniques LITT, RF-TC and SRS concluded that LITT shows promising seizure efficacy in the short-term ( 65 ). Our linear-regression model results provide a much-needed statistical analysis of the data in comparison to open surgical methods to further support LITT as an emerging technique, but long-term follow ups and direct comparisons are needed to form a firm conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Focused ultrasound also has a potential use for neuromodulation in epilepsies 29 . There is compelling evidence of efficacy for these emerging minimally invasive approaches, 30,31 but recent meta‐analyses suggest waning seizure freedom over time across all types of epilepsy surgery, most noticeable in minimally invasive approaches 32,33 . Overall, rigorous research is still needed to adequately resolve controversies regarding the long‐term risks and benefits.…”
Section: Critical Definitions and Conceptsmentioning
confidence: 99%
“…Over the last decade, multiple case series have reported promising short-term results of LITT in DRE. Two recent systematic reviews showed that seizure-freedom after LITT ranges between 33 and 77.8%; however, the long-term Engel I outcomes have been shown to decrease to 50% after 5 years of follow-up [40,44]. LITT has higher rates (60-89%) of seizure-freedom in DRE associated with mesial temporal sclerosis and hypothalamic hamartomas [40].…”
Section: Advancements In Minimally Invasive Proceduresmentioning
confidence: 99%
“…Two recent systematic reviews showed that seizure-freedom after LITT ranges between 33 and 77.8%; however, the long-term Engel I outcomes have been shown to decrease to 50% after 5 years of follow-up [40,44]. LITT has higher rates (60-89%) of seizure-freedom in DRE associated with mesial temporal sclerosis and hypothalamic hamartomas [40]. Moreover, recent studies have reported better naming and object recognition outcomes after LITT in dominant hemisphere epilepsy compared with standard ATL [45].…”
Section: Advancements In Minimally Invasive Proceduresmentioning
confidence: 99%